The Dokounta of the Platonic Dialectician. On Plato’s distinction between the insufficient "present discussion" and a satisfactory future one - Szlezák, Thomas Alexander (Peitho. Examina Antiqua, 2015)
It is a recurring pattern in Plato´s dialogues that the dialectician leads the discussion to a certain point where he identifies further, more fundamental problems, on which he claims to have his own view (to emoi dokoun, vel sim.), which he does not communicate. Such passages are briefly analyzed from five dialogues (Timaeus, Sophist, Politicus, Parmenides, Republic). It is shown that this seemingly strange behaviour of the dialectician corresponds exactly to the way a philosopher should behave according to the Phaedrus. The recurring cases of reticence of the leading figure in dialogue have to be understood as Plato´s written reference to his own unwritten philosophy.